ANALISIS PENGARUH MANAJEMEN MODAL KERJA, LIKUIDITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA - Rika Sustia; Tohir Tohir (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2013)
The profitability of manufacturing companies in Indonesia is influenced by a variety of financial factors that can be measured by using financial ratios. This research was conducted to analyze weather the working capital management, liquidity, leverage and firm size influence on the company's profitability measured by return on assets (ROA). The sample in this research was taken using purposive sampling method, in order to get 29 companies manufacturing consumer goods industries listed on the Indonesia Stock Exchange (BEI) in the year 2009-2011. The influence of independent variables such as receivables collection period (RCP), inventory conversion period (ICP), payable deferral period (PDP), current ratio (CR), debt ratio (DR) and the size of the company to the return on assets was investigated using multiple linear regression analysis method. The results showed that the variables of the receivables collection period, inventory conversion period and firm size have negative effect on return on assets and current ratio has positive effect on return on assets. While the payable deferral period and debt ratio variables have no impact on return on assets.